Identifying barriers and enablers to participation in infection surveillance in Australian residential aged care facilities - Eliza Watson; Leslie Dowson; David Dunt; Karin Thursky; Leon J. Worth; Janet K. Sluggett; Amanda Appathurai; Noleen Bennett; for the National Infection Surveillance Program in Aged Care (NISPAC) (BMC, 2023)
Abstract Background Infection surveillance is a vital part of infection prevention and control activities for the aged care sector. In Australia there are two currently available infection and antimicrobial use surveillance programs for residential aged care facilities. These programs are not mandated nor available to all facilities. Development of a new surveillance program will provide standardised surveillance for all facilities in Australia. Methods This study aimed to assess barriers and enablers to participation in the two existing infection and antimicrobial use surveillance programs, to improve development and implementation of a new program. A mixed-methods study was performed. Aged Care staff involved in infection surveillance were invited to participate in focus groups and complete an online survey comprising 17 items. Interviews were transcribed and analysed using the COM-B framework. Results Twenty-nine staff took part in the focus groups and two hundred took part in the survey. Barriers to participating in aged care infection surveillance programs were the time needed to collect and enter data, competing priority tasks, limited understanding of surveillance from some staff, difficulty engaging clinicians, and staff fatigue after the COVID-19 pandemic. Factors that enabled participation were previous experience with surveillance, and sharing responsibilities, educational materials and using data for benchmarking and to improve practice. Conclusion Streamlined and simple data entry methods will reduce the burden of surveillance on staff. Education materials will be vital for the implementation of a new surveillance program. These materials must be tailored to different aged care workers, specific to the aged care context and provide guidance on how to use surveillance results to improve practice.